(untitled) (Journal of Science and Technology, 2016)
Plants of Centrosema pubescens, Lablab purpureus and Stylosanthes guianensis grown sepa- rately in pots under green house conditions, were subjected to moisture stress conditions of 100, 75, 50, and 25% field capacity (FC) and the effect on plant growth characteristics assessed. Soil moisture stress significantly reduced plant height, shoot and root dry weights, particularly in Lablab and Stylosanthes. Root/shoot ratio on the other hand increased as soil moisture regime decreased. A change in moisture stress from 100 to 25 % FC reduced nodule numbers by 37, 19 and 9 % in Lablab, Stylosanthes and Centrosema respectively and decreased nitrogen fixed by 32, 9, and 0.4 % in Stylosanthes, Lablab and Centrosema respectively. The mean P content of the plants decreased with decreasing soil moisture content while, that of K increased as moisture stress increased. The overall plant performance pointed to Centrosema as a more favoured for- age plant for dry environments .